A numerical analysis of windscreen effects on air-cooled condenser fan performance. (5th March 2021) - Venter, A.J.; Owen, M.T.F.; Muiyser, J.
Highlights: Peripheral windscreens hinder ACC fan performance at low to moderate wind speeds. Peripheral windscreens can bolster fan performance of tall ACCs at high wind speeds. Windscreen height, platform height and wind speed are key parameters in the assessment of windscreen effects. Abstract: Porous peripheral windscreens are used to mitigate adverse effects of wind on air-cooled condenser (ACC) fan performance and dynamic blade loading. However, the effects of this measure on fan performance are not comprehensively understood and the relevant literature is largely inconsistent. In this study, an experimental ACC fan row test facility is replicated numerically in a computational fluid dynamics (CFD) analysis. Numerical modelling techniques are validated using experimental results and used to perform a parametric assessment of windscreen effects. The results from this parametric assessment are unpacked to provide insight into the mechanisms that determine the effect of peripheral windscreens on ACC fan performance, as well as the reasons for the inconsistency in the prior literature. The results indicate that peripheral windscreens mostly hinder fan performance at low wind speeds; however, favourable enhancement is attainable depending on the configuration of the windscreen height, fan platform height and the wind speed condition. For the particular cases investigated, the results suggest that peripheral windscreens, covering 50% or more of the peripheral inlet area, are beneficial for tall platform height ACCs ( H/df, ≥2.5) at wind speeds greater than 16 m/s (velocity at full-scale platform height), while for lower platform height ACCs, a similar peripheral windscreen (same dimensionless height) will only offer a beneficial effect at even greater wind speeds.